PENGEMBANGAN MEDIA FLASH CARD INTERAKTIF BERBASIS KEARIFAN LOKAL PADA MATA PELAJARAN MATEMATIKA KELAS IV SEKOLAH DASAR FLASHCARD INTERAKTIF BERBASIS KEARIFAN LOKAL PADA MATA PELAJARAN MATEMATIKA KELAS IV SEKOLAH DASAR NEGERI 2 SIDETAPA - Putu Jodi Angga Perdana; I Putu Suardipa; I Ketut Suparya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop Interactive Flash Card Learning Media Based on Local Wisdom in Mathematics Subjects for Grade IV of Sidetapa 2 Elementary School. The method used in this study is Research and Development (R&D) with the ADDIE model approach which includes the stages of Analysis, Design, Development, Implementation, Evaluation. The research subjects consisted of three expert validators (media, language, materials), two class teachers and thirty-seven grade IV students of Sidetapa 2 Elementary School. The results of the study show that: (1) Interactive Flash card products based on local wisdom were developed using the Canva and Quiziz applications for the quizzes to attract students' interest in learning. (2) Validity results indicate that the developed interactive flashcard media based on local wisdom is categorized as very valid, with a media validity score of 0.92, language validity of 0.88, and material validity of 0.9. (3) Practicality test results indicate that this media is very practical to use, with a teacher practicality rating of 97% and a student practicality rating of 97.6%. Based on these results, this interactive flashcard media based on local wisdom is very valid and very practical for use in mathematics learning activities in grade IV of SD Negeri 2 Sidetapa.